The Relationship Between Physical Activity and Mental Health: A Literature Review - Purnomo, Purnomo (Journal of Salutare, 2025)
Biddle, S. J. H., Ciaccioni, S., Thomas, G., & Vergeer, I. (2019). Physical activity and mental health in children and adolescents: An updated review of reviews and an analysis of causality. Psychology of Sport and Exercise, 42, 146–155. https://doi.org/10.1016/j.psychsport.2018.08.011 Bull, F. C., Al-Ansari, S. S., Biddle, S., Borodulin, K., Buman, M. P., Cardon, G., ... & Willumsen, J. F. (2020). World Health Organization 2020 guidelines on physical activity and sedentary behaviour. British Journal of Sports Medicine, 54(24), 1451–1462. https://doi.org/10.1136/bjsports-2020-102955 Czosnek, L., Lederman, O., Cormie, P., Zopf, E., Stubbs, B., & Rosenbaum, S. (2019). Health benefits, safety and cost of physical activity interventions for mental health conditions: A meta-review to inform translation efforts. Mental Health and Physical Activity, 16, 140–151. https://doi.org/10.1016/j.mhpa.2018.11.001 Dishman, R. K., Heath, G. W., & Lee, I. M. (2021). Physical activity epidemiology (3rd ed.). Human Kinetics. Firth, J., Solmi, M., Wootton, R. E., Vancampfort, D., Schuch, F. B., Hoare, E., ... & Smith, L. (2020). A meta-review of “lifestyle psychiatry”: The role of exercise, smoking, diet and sleep in the prevention and treatment of mental disorders. World Psychiatry, 19(3), 360–380. https://doi.org/10.1002/wps.20773 Kandola, A., Ashdown-Franks, G., Hendrikse, J., Sabiston, C. M., & Stubbs, B. (2019). Physical activity and depression: Towards understanding the antidepressant mechanisms of physical activity. Neuroscience & Biobehavioral Reviews, 107, 525–539. https://doi.org/10.1016/j.neubiorev.2019.09.040 Kaur, S., & Sharma, R. (2022). Impact of physical activity on stress, anxiety, and depression in college students. International Journal of Adolescence and Youth, 27(1), 123–135. https://doi.org/10.1080/02673843.2022.2030253 Keating, X. D., Zhou, K., Liu, X., & Guan, J. (2020). Effects of physical activity on mental health in university students. College Student Journal, 54(1), 16–28. McDowell, C. P., Dishman, R. K., Gordon, B. R., & Herring, M. P. (2019). Physical activity and depression: A review of reviews. Current Opinion in Psychology, 32, 141–147. https://doi.org/10.1016/j.copsyc.2019.07.020 Mikkelsen, K., Stojanovska, L., Polenakovic, M., Bosevski, M., & Apostolopoulos, V. (2019). Exercise and mental health. Maturitas, 124, 40–47. https://doi.org/10.1016/j.maturitas.2019.03.005 O'Hara, L., O'Connor, J., & Whelan, E. (2020). The public perception of physical activity in mental health care. International Journal of Environmental Research and Public Health, 17(13), 4816. https://doi.org/10.3390/ijerph17134816 Rebar, A. L., Stanton, R., Geard, D., Short, C., Duncan, M. J., & Vandelanotte, C. (2020). A meta-meta-analysis of the effect of physical activity on depression and anxiety in non-clinical adult populations. Health Psychology Review, 14(2), 294–308. https://doi.org/10.1080/17437199.2019.1627897 Rosenbaum, S., Morell, R., Abdel-Baki, A., Ahmadpanah, M., Anilkumar, T. V., Baie, L., ... & Vancampfort, D. (2020). International Organization of Physical Therapists in Mental Health consensus statement on physical activity and exercise for mental health promotion. Journal of Mental Health, 29(3), 246–255. https://doi.org/10.1080/09638237.2019.1616136 Schuch, F. B., Vancampfort, D., Firth, J., Rosenbaum, S., Ward, P. B., Silva, E. S., ... & Stubbs, B. (2019). Physical activity and sedentary behavior in people with major depressive disorder: A systematic review and meta-analysis. J Affect Disord., 210, 1–13. https://doi.org/10.1016/j.jad.2016.10.050 Sharma, A., & Mandal, S. (2021). The effects of physical activity on mental health and well-being: A systematic review. Mental Health Review Journal, 26(1), 21–33. https://doi.org/10.1108/MHRJ-10-2020-0060 Stubbs, B., Vancampfort, D., Rosenbaum, S., Firth, J., Cosco, T., Veronese, N., ... & Schuch, F. B. (2019). An examination of the anxiolytic effects of exercise for people with anxiety and stress-related disorders: A meta-analysis. Psychiatry Research, 249, 102–108. https://doi.org/10.1016/j.psychres.2016.12.020 Teychenne, M., Costigan, S. A., & Parker, K. (2020). The association between sedentary behaviour and risk of anxiety: A systematic review. BMC Public Health, 15, 513. https://doi.org/10.1186/s12889-015-1843-x Vancampfort, D., Firth, J., Schuch, F. B., Rosenbaum, S., Mugisha, J., Hallgren, M., ... & Stubbs, B. (2019). Physical activity and sedentary behavior in people with major depressive disorder: A systematic review and meta-analysis. J Affect Disord., 210, 1–13. https://doi.org/10.1016/j.jad.2016.10.050 White, R. L., Babic, M. J., Parker, P. D., Lubans, D. R., & Astell-Burt, T. (2021). Domain-specific physical activity and mental health: A meta-analysis. American Journal of Preventive Medicine, 60(2), 240–251. https://doi.org/10.1016/j.amepre.2020.08.014 WHO. (2022). World mental health report: Transforming mental health for all. World Health Organization. https://www.who.int/publications/i/item/9789240049338